(untitled) (Global Journal of Science Frontier Research, 2020)
The physics of Kelvin’s dropper is still not completely understood, since it is unclear how neutral drops of water, even when polarized, can acquire a unitary charge. The article suggests that the process of acquiring a unitary charge by droplets in a Kelvin dropper is similar to acquiring charges by raindrops falling from a thundercloud. Therefore, a thundercloud, judging by the physical processes occurring in it, represents a giant Kelvin dropper.